Carbon paste electrodes bulk-modified with carbon nanotubes and chemically oxidized carbon nanotubes for the determination of hydrogen peroxide - Zbiljić, Jasmina; Vajdle, Olga; Guzsvány, Valéria; Kónya, Zoltán; Kukovecz, Ákos; Dalmacija, Božo; Kalcher, Kurt (Univerzita Pardubice, 2014)
Carbon paste electrodes (graphite/paraffin oil) bulk-modified with multiwalled carbon nanotubes (MWCNT) and chemically oxidized MWCNT (O-MWCNT) were used as sensors for the hydrodynamic chronoamperometric determination of hydrogen peroxide (H2O2). Experimental parameters, such as the type and pH of the supporting electrolyte or the working potential(s) applied were investigated in the batch arrangement.
Keywords: carbon paste electrode; bulk modification; MWCNT; O-MWCNT; hydrodynamic chronoamperometry; hydrogen peroxide